Onset of convection in a dielectric nanofluid saturated anisotropic porous medium - Shamsudin, Nur Aisyah Maisara; Mohd Mokhtar, Nor Fadzillah (Academy of Sciences Malaysia, 2019)
The onset of thermal convection in a horizontal layer of a dielectric nanofluid saturated an anisotropic porous medium with vertical AC(alternate current) electric field has been studied. We considered Darcy model for porous medium while for nanofluid model used, it incorporates the effects of thermophoresis, electrophoresis and Brownian motion. A linear stability analysis based upon a normal mode has been performed, and the expression of thermal Rayleigh number is obtained using the Galerkin method. The results show that an increase value of AC electric Rayleigh number, Re and mechanical anisotropy parameter, ξ is to destabilize the system of nanofluid layer while the thermal anisotropy parameter, η has stabilizing effect on the onset of electroconvection.